Priorização de necessidades de saúde na consulta de enfermagem de pré-natal na estratégia saúde da família - Miranda, Eglivani Felisberta (2013)
The pregnant woman presents countless needs in the organic health, psycho emotional and socio-cultural, which should constitute objects of the prenatal assistance, in an overarching and specific manner, although it hardly ever occurs. So this research focuses on the process of the election of the health needs in the prenatal units of Family Health Strategy in Cuiabá, Mato Grosso. That aims to analyse how it arranges itself on the prioritizing the women needs during the appointments of a prenatal nurse. It is a descriptive, qualitative research, done in four units, through systematic participative observation of 50 medical appointments, the open interview with the nurses, analysis of 79 records of consultations observed, and analysis of thematic content of the empirical material. The nurses prioritize an approach of certain physics aspects of the pregnancy: discomfort in the first trimester, feed aspects and weight changing, vitality conditions, uterine accommodation and the growing of the conceptus, structure features of the breast that may compromise the breast feeding, risks and/or medical intercurrent with possible repercussions to the woman and/or to the newborn. Nurses also address some aspects related to the psycho-emotional and social health of pregnant women, but these are not part orderly attendance. The women bring to the medical appointment several needs: psycho emotional, concerns related to family conflict due to inappropriate social-economics condition, information related to theirs and the conceptus’ health condition, access to health resources and participation of the family during the service. Despite the mobilizing factor of these needs, they do not change the priorities established during the appointments. The clinic of the nurse, focused on the approach of the organic needs, reveals limits, even though it also corresponds to the indicated nationally and internationally, the avoidance of death of the mother and the newborn. The services are standardized. In the election of the organic needs, there are flaws on the collection of the previous/current clinic history and in the realization of the complete physical exams. The nurse does not use several technologies during medical appointments and occupies his own centre. The diagnostics definitions are considered only objective data and coming from exams results, whereas several are not considered. The diagnostics invariably are common to several women and its behaviors concentrate in the actions of prenatal routine. Besides that, the stages of methodology of the assistance are adopted partially or done incompletely. The clinic of the nurse does not reveal specificity, effecting in the forms of the medical clinic. The professional has a conception of the practice which emphasizes the approach of the organic needs and the access of the woman to the health service, despite recognizing that she has psycho emotional, social, educational and family needs. For the election of the needs, it is emphasized the traditional technologies: the interview, the physical exams and results of the laboratories exams and ultrasound. The nurses judge the pregnant woman participative during the appointment and naturalize the control they have over the pregnant women. The methodology of the assistance is interpreted as a tool that leads the assistance, but not in its potential to the effectiveness on the specific nursing care. It is necessary to invest in improvements of the processes of basic attention works, in the formation and education of nurses, adding to the increase of approaches of the prenatal needs, especially, through the practice of a clinic which has as a label, not only quality, but also the breadth and specificity.